The Relationship of Perceived Benefit, Perceived Barrier, and Knowledge with Vaccine Hesitancy among Anti- and Pro- Vaccine Community - Aisyah Nur Izzati; Retno Indarwati; Makhfudli (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: The phenomenon of basic vaccine hesitancy in parents is the biggest challenge faced byhealth workers in the global era currently. This study aimed to analyze the relationship between perceivedbenefits, perceived barriers, and knowledge about vaccines towards vaccine hesitancy among anti and provaccinecommunities on social media Facebook.Methods: This study used a cross-sectional design. The sample was 150 members of the anti-vaccinecommunity and 234 members of the pro-vaccine community on social media Facebook using a purposivesampling technique. Data were collected using questionnaire namely; HBM (health belief model)questionnaire which was translated and modified, and Vaccine Hesitancy Scale (VHS) questionnaire. Theindependent variables in this study were perceived benefits of vaccines, perceived barriers to vaccines,knowledge about vaccines. The dependent variable was vaccine hesitancy. Spearman rho analysis was usedto measure the relationship between the dependent and independent variables.Results: The results of the Spearman rho analysis showed that the perceived benefits of vaccines (p=0.363of anti-vaccine, p=0.702 of pro-vaccine), the perceived barriers to vaccines (p=0.410 of anti-vaccine,p=0.341 of pro-vaccine), and knowledge about vaccines (p=0.413 of anti-vaccine, p=0.192 of pro-vaccine)was related to vaccine hesitancy in parents.Discussion: This study results indicated that the perceived benefits of vaccines, perceived barriers tovaccines, and knowledge about vaccines are related to vaccine hesitancy in parents. The implications of thestudy are essential information for health workers to determine the right and wise strategy in responding tothe increasing vaccine hesitancy in public so that basic vaccine coverage will increase.